Research trend in latex harvesting of rubber tree (Hevea brasiliensis Muell. Arg.) based on bibliographic analysis - Junaidi, Junaidi (2022)
The rubber plant (Hevea brasiliensis Muell. Arg.) is the main natural rubber-producing species. Researches on rubber has been carried out for more than a century. Researchers and academics should stay up to date with the current scientific issues including latex harvesting in H. brasiliensis Muell. Arg. This article presents a bibliometric analysis of scientific literature indexed by Scopus and published from 2018 to 2022. The literature was categorized into three sub-topics i.e., latex harvesting techniques (38 papers), physiological mechanisms (41 papers), and oxidative stress induced by latex harvesting practices (18 papers). Metadata validation was performed using Mendeley reference management software and bibliometric analysis was carried out using VOSviewer bibliometric network visualization software. The results on the latex harvesting technique showed that most of the articles were related to the development of automatic tapping machines. This indicates a trend that latex harvesting techniques are likely shifting from manual tapping to fully automated methods using machines and robots. In terms of physiological mechanisms related to latex production, the mechanism of rubber biosynthesis and ethylene response at the genomic, transcriptomic, and proteomic levels predominated the finding. Research on oxidative stress induced by tapping mainly focuses on the effects of mechanical wounding and ethylene stimulation, while research on antioxidants is still limited. In the past five years, biotechnology and molecular analysis are the main tools to study physiological mechanisms and oxidative stress. This can be a consideration for scientists and research institutions to develop laboratories and human resources to be able to conduct molecular-based research.